Examining the dynamic and nonlinear impacts of public health events on the resilience of food supply chain: evidence from China - Li, Jingdong; Li, Zhi; Shi, Zilong; Geng, Hongjun (Frontiers in Sustainable Food Systems, 2024)
Introduction The fragility of agriculture makes the food supply chain vulnerable to external risks such as epidemic, conflict, disaster, climate change, economic and energy crisis. The COVID-19 pandemic has spread and continued globally in recent years, resulting in food supply chain disruption and insecurity, which triggers profound reflection on the impacts of public health events (PHEs). Studying the impacts of PHEs on the resilience of food supply chain has great significance to effectively reduce the risks of disruption and insecurity in the future. Methods Based on the composition of PHEs and the division of food supply chain, this paper adopted the nonlinear Granger causality test to verify the nonlinear causal relationship between PHEs and proxy variables in the food supply chain; then the TVP-VAR-SV model was constructed and its three-dimensional pulse response results were matched with the sensitivity, recovery, and adaptation of the food supply chain resilience to deeply explore the dynamic impacts of PHEs. Results PHEs has significant nonlinear conduction effects on the resilience of food supply chain, the impacts of PHEs on the partial sector resilience have significant dynamic characteristics in the whole sample period, and the impacts of PHEs on the recovery and adaptation aspects of food supply chain resilience have structural break characteristics. Discussion The differences, dynamic characteristics and structural breaks of the impacts of PHEs on the resilience of food supply chain are caused by the infectivity and mortality of PHEs, attributes of food products, regulation of supply and demand in the market, behavioral decisions of all participants, changes in the policy environment, and coordination and upgrading of all sectors in the supply chain.